Correction to: Mobile phone data reveals the importance of pre-disaster inter-city social ties for recovery after Hurricane Maria - Yabe, Takahiro; Ukkusuri, Satish V.; Rao, P. Suresh C. (Applied network science, 2020)
Following publication of the original article [1], the author reported to remove the name from the acknowledgements in the original article.